2004
DOI: 10.1002/bit.20166
|View full text |Cite
|
Sign up to set email alerts
|

Molecular understanding of oxygen‐tension and patient‐variability effects on ex vivo expanded T cells

Abstract: Immunotherapy with ex vivo cultured T cells depends on a large supply of biologically active cells. Understanding the effects of culture parameters is essential for improving the proliferation and efficacy of the expanded cells. Low oxygen tension (5% pO(2)) was previously reported to improve T-cell expansion and alter cellular phenotypic characteristics compared to T cells cultured at 20% pO(2). Here we report the use of DNA-array based transcriptional analysis coupled with protein-level analysis to provide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…Consistent with this argument, a recent report by Haddad et al (15) showed that the expression of genes important in lymphocyte function (e.g., granzyme A) is increased in cells cultured at 5% oxygen, whereas the expression of genes involved in stress response, cell death, and cellular repair was elevated at 20% oxygen. Although these studies were conducted with PBMCs from hemachromatosis subjects, the findings point to differences in gene expression that are likely to occur in cultures of cells from healthy donors and are consistent with the differential responsiveness of lymphocytes that we observed at different oxygen levels.…”
Section: Discussionmentioning
confidence: 55%
“…Consistent with this argument, a recent report by Haddad et al (15) showed that the expression of genes important in lymphocyte function (e.g., granzyme A) is increased in cells cultured at 5% oxygen, whereas the expression of genes involved in stress response, cell death, and cellular repair was elevated at 20% oxygen. Although these studies were conducted with PBMCs from hemachromatosis subjects, the findings point to differences in gene expression that are likely to occur in cultures of cells from healthy donors and are consistent with the differential responsiveness of lymphocytes that we observed at different oxygen levels.…”
Section: Discussionmentioning
confidence: 55%
“…The mitogen induced PBMCs show increased intracellular nitric oxide levels and reduced intracellular glutathione levels at 20% oxygen [17, 18]. Haddad et al, showed the increase in expression of genes involved in cell death, cellular repair, and stress response in primary T-cells maintained at atmospheric O 2 levels indicating increased oxidative stress response [48]. Cultivation of rat liver sinusoidal endothelial cells (LSECs) at 5% O 2 , as opposed to 21% O 2 improved the survival of LSECs and scavenger receptor-mediated endocytic activity, reduced the production of the pro-inflammatory mediator, interleukin-6 and increased the production of the anti-inflammatory cytokine, interleukin-10 [49].…”
Section: Activation Of Redox Sensitive Inflammatory Signalingmentioning
confidence: 99%
“…Several studies indicate that incubator oxygen levels can modulate the metabolism (2, 4), gene expression (5,6), and function of primary cells (3,(7)(8)(9). However, the significance of these findings is obscured because the current notation for describing incubator oxygen levels is very confusing: atmospheric oxygen levels are typically referred to as ''normoxic,'' even though these levels are substantially above the levels animal cells normally encounter in vivo.…”
mentioning
confidence: 97%